GAMBARAN INTERAKSI OBAT PENYAKIT JANTUNG KORONER DENGAN SINDROM METABOLIK PADA PASIEN RAWAT JALAN DI RS TK II DR. SOEPRAOEN MALANG - Aprilianti, Rakhmadani Gadis; Sekti, Beta Herilla; Hidayati, Lilik Nur (Jurnal Riset Kefarmasian Indonesia, 2022)
Drug interaction is the effect of a drug that is caused when there are two or more drugs that interact and affect the body's response to treatment. The method used in this study is a descriptive study using a cross-sectional observational method with retrospective observations in October - December 2020. Patient data collection was obtained from patient medical records using a purposive sampling technique with inclusion criteria. A total of 89 patients were taken as samples. Data analysis using MEDSCAPE and drugs.com applications. A total of 82 prescriptions have the potential for drug interactions, where the most significant level of drug interaction is moderate level (81.48%, these include aspirin with candesartan and bisoprolol with amlodipine. The most drug interaction is the interaction between aspirin and bisoprolol which is classified as a minor interaction (17.74%). The most frequently used type of drug is bisoprolol (22.18%) and the most frequently used drug class is beta blocker